ANALISA PENGOPERASIAN 1 CWP DAN 2 CWP PADA COOLING WATER SYSTEM PLTU ASAM ASAM UNIT 4 - Juni Eko Hartanto; Mastiadi Tamjidillah (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2019)
Electric power is used to support daily life, therefore electrical energy must be continually developed considering the increasing need for this energy. Therefore it is necessary to do preventive, corrective maintenance and efforts to optimize the generating unit such as savings in the production process, one of which is by analyzing the operation of a Circulating Water Pump CWP at the Unit 4 Acid-Acid Power Plant. The formulation of the problem in this study is that in the manufacturer's design for 65 MW full load 2 CWP pumps are needed, this can be seen from the pump specification data, but in fact with only a Circulating Water Pump CWP can produce a full load of 65 MW.